Saving Lives and Preventing Injuries From Unjustified Protective Actions—Method for Developing a Comprehensive Public Protective Action Strategy for a Severe NPP Emergency. Issue 5 (May 2018) - Callen, J.; McKenna, T.
Abstract : Abstract: During the response to the Fukushima Daiichi nuclear power plant (FDNPP) emergency, about 50 patients died during or shortly after an evacuation when they were not provided with the needed medical support. In addition, it has been shown that during the FDNPP emergency there were increases in mortality rates among the elderly due to long-term dislocation as a result of evacuation and relocation orders and an inability to stay in areas where residents were advised to shelter for extended periods. These deaths occurred even though the possible radiation exposure to the public was too low to result in radiation-induced deaths, injuries, or a meaningful increase in the cancer rate, even if no protective actions had been taken. These problems are not unique to the FDNPP emergency and would be expected if the recommendations of many organizations were followed. Neither the International Commission on Radiological Protection (ICRP), the U.S. Nuclear Regulatory Commission (NRC) nor the U.S Environmental Protection Agency (EPA) adequately take into consideration in their recommendations and analysis the non-radiological health impacts, such as deaths and injuries, that could result from protective actions. Furthermore, ICRP, NRC, EPA, and the U.S. Department of Homeland Security (DHS) call for taking protective actions at doses lower than those resulting in meaningful adverse radiation-induced health effects and do not state the doses at which such effects would be seen. Consequently, it would be impossible for decision makers and the public to balance all the hazards both from radiation exposure and protective actions when deciding whether a protective action is justified. What is needed, as is presented in this paper, is a method for developing a comprehensive protective action strategy that allows the public, decision makers, and others who must work together to balance the radiological with the non-radiological health hazards posed by protective actions, and to counter the exaggerated fear of radiation exposure that could lead to taking unjustified protective actions and adverse psychological, sociological, and other effects.